Dynamic Testing of Instructional Needs: A Training-Only Graduated Prompts Approach - Veerbeek, Jochanan; Vogelaar, Bart (Journal of psychoeducational assessment, 2025)
Dynamic testing, though underutilized, holds potential for assessing learning and instructional needs. However, its limited adoption is often attributed to the perceived time and labor-intensive nature of its administration. This study explores the viability of a training-only dynamic test (ToDT) with a standardized procedure to identify instructional needs in school children. The study involved 66 fourth and fifth-grade students (M age = 10.89 years, SD = 0.53) and analyzed the relations between ToDT scores (number and type of hints), teachers’ estimations of instructional needs, and standardized math and reading scores. Results revealed moderate to strong correlations between ToDT scores, teachers’ estimations, and standardized scores. Additionally, children with different classifications based on ToDT scores differed in their instructional needs and standardized test scores. This study not only underscores the potential of the training-only dynamic test (ToDT) in gauging instructional needs, but also revealed distinct needs and outcomes based on their ToDT scores.